2009
DOI: 10.1021/nn9011384
|View full text |Cite
|
Sign up to set email alerts
|

A Calibration Method for Nanowire Biosensors to Suppress Device-to-Device Variation

Abstract: Nanowire/nanotube biosensors have stimulated significant interest; however the inevitable device-to-device variation in the biosensor performance remains a great challenge. We have developed an analytical method to calibrate nanowire biosensor responses that can suppress the device-to-device variation in sensing response significantly. The method is based on our discovery of a strong correlation between the biosensor gate dependence (dIds/dVg) and the absolute response (absolute change in current, ΔI). In2O3 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
136
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(145 citation statements)
references
References 55 publications
4
136
1
Order By: Relevance
“…1A,B). The resulting 144 nanosensor devices were electrically characterized and effectively normalized by their respective transconductance values, thus minimizing the device-to-device signal variability 30 , Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A,B). The resulting 144 nanosensor devices were electrically characterized and effectively normalized by their respective transconductance values, thus minimizing the device-to-device signal variability 30 , Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, the calibrated responses of the devices to the analyte (DI sd ), when normalized by their respective transconductance values (device transconductance ðG m ¼ dIds dVg Þ), Fig. 2b, will result in relatively small device-to-device variability, even for originally largely dissimilar devices 30 , Fig. 2c.…”
Section: Article Nature Communications | Doi: 101038/ncomms5195mentioning
confidence: 99%
“…119 The reason for this reduction in device-to-device ratio is that the absolute current is directly dependent upon geometric parameters and threshold voltage of the device, whereas the normalised change in current is only subject to device-to-device variation from differences in the device threshold voltage. 119 Further, the change in current (ΔI) can either be positive or negative and consequently the normalised change in current, I norm , also has an associated sign. Some authors have reported the normalised change in current without this sign which makes the polarity of the measured change ambiguous.…”
Section: Analysis Of Sensitivitymentioning
confidence: 99%
“…In the subthreshold region, the transconductance is variable as a function of gate voltage and therefore cannot be treated as a constant. For FET-sensors operated in the linear regime, ΔV T can be extracted experimentally by simply dividing the current-response data (ΔI) by the device transconductance, g m : 29,61,119,128 …”
Section: 127mentioning
confidence: 99%
See 1 more Smart Citation